The IAXO Helioscope. (October 2015) - Ribas, E Ferrer; Armengaud, E; Avignone, F T.; Betz, M; Brax, P; Brun, P; Cantatore, G; Carmona, J M.; Carosi, G P; Caspers, F; Caspi, S; Cetin, S A; et al.
Abstract: The IAXO (International Axion Experiment) is a fourth generation helioscope with a sensitivity, in terms of detectable signal counts, at least 10 4 better than CAST phase-I, resulting in sensitivity on gaγ one order of magnitude better. To achieve this performance IAXO will count on a 8-coil toroidal magnet with 60 cm diameter bores and equipped with X-ray focusing optics into 0.20 cm 2 spots coupled to ultra-low background Micromegas X-ray detectors. The magnet will be on a platform that will allow solar tracking for 12 hours per day. The next short term objectives are to prepare a Technical Design Report and to construct the first prototypes of the hardware main ingredients: demonstration coil, X-ray optics and low background detector while refining the physics case and studying the feasibility studies for Dark Matter axions.